Roland Barthes' Semiotic Analysis of Prabowo - Gibran's Use of Fashion in the 2024 Presidential Election - Tamba, Kezya Yunsi; Sukmarini, Andi Vita; Arief, Abdul Samad (Journal La Sociale, 2026)
Fashion as a form of political communication during the 2024 Presidential Election in Indonesia, this study aims to explore how fashion was utilized as a medium of political communication by the presidential and vice-presidential candidates Prabowo Subianto and Gibran Rakabuming Raka, with a focus on the visual representations displayed through the social media platform Instagram. In this context, fashion is not merely seen as a matter of clothing style, but as a set of signs that carry political, symbolic, and ideological meanings. This research employs a qualitative method through a literature study by analyzing various scholarly sources and visual documentation obtained from the official Instagram account @prabowo.gibran2. The theoretical framework is based on Roland Barthes’ semiotic theory, which outlines the process of meaning-making through three key stages: denotation (literal meaning), connotation (cultural meaning), and myth (the underlying ideological narrative within signs). The findings reveal that the fashion choices worn by Prabowo-Gibran during the campaign conveyed strong nonverbal political messages. For instance, Prabowo’s signature militaristic style constructed an image of firmness and nationalism. Meanwhile, Gibran’s light blue varsity jacket adorned with anime motifs highlighted youth identity and a non-conventional approach to politics. Most iconically, the frequent use of light blue shirts and casual clothing represented simplicity, a sense of closeness to the people, and youthful energy. These meanings were visually constructed and consistently repeated across various posts, forming a political myth that portrayed Prabowo-Gibran as an ideal duo combining seasoned leadership with youthful vigor.